Synthesis, enantioseparation and photophysical properties of planar-chiral pillar[5]arene derivatives bearing fluorophore fragments - Li, Guojuan; Fan, Chunying; Cheng, Guo; Wu, Wanhua; Yang, Cheng (Beilstein Journal of Organic Chemistry, 2019)
Planar chiral pillar[5]arene derivatives (P5A-DPA and P5A-Py) bearing bulky fluorophores were obtained in high yield by click reaction. The photophysical properties of both compounds were investigated in detail. P5A-DPA with two 9,10-diphenylanthracene (DPA) pigments grafted on the pillar[5]arene showed a high fluorescence quantum yield of 89.5%. This is comparable to the monomer DPA-6, while P5A-Py with two perylene (Py) pigments grafted on the pillar[5]arene showed a significantly reduced quantum yield of 46.4% vs 78.2% for the monomer Py-6. The oxygen-through-annulus rotation of the phenolic units was inhibited for both compounds due to the bulky chromophore introduced, and the resolution of the enantiomers was achieved due to the bulky size of the fluorophores. The absolute configuration of the enantiomers was determined by circular dichroism (CD) spectra. The solvent-induced aggregation behavior was investigated with the enantiopure P5A-DPA and P5A-Py. It was found that the CD signals were enhanced by aggregation. P5A-DPA showed aggregation-induced emission enhancement, while P5A-Py showed aggregation-induced emission quenching, accompanied by excimer emission when aggregating in water and THF mixed solution.
Keywords: aggregation; circular dichroism; chirality; click chemistry; macrocycles; pillar[5]arenes